Tracking trends in the extinction risk of wild relatives of domesticated species to assess progress against global biodiversity targets. Issue 1 (27th June 2018) - McGowan, Philip J.K.; Mair, Louise; Symes, Andrew; Westrip, James R.S.; Wheatley, Hannah; Brook, Sarah; Burton, James; King, Sarah; McShea, William J.; Moehlman, Patricia D.; Smith, Andrew T.; Wheeler, Jane C.; et al.
Abstract: Ensuring the conservation of wild relatives of domesticated animals that are important food sources for humans forms part of targets for both the Convention on Biological Diversity (CBD) and the Sustainable Development Goals (SDG). There is, however, no indicator allowing progress toward these aims to be measured. We identified 30 domesticated mammal and bird taxa that are sources of food for humans and consider 55 mammal and 449 bird species to be their wild relatives. We developed a Red List Index for these wild relatives, which declined by 2.02% between 1988 and 2016. Currently, 15 species are Critically Endangered, indicating that the Red List Index could deteriorate sharply unless action is taken to ensure the survival of highly threatened species and the reversal of their declines. This Index can meet a range of global policy needs, including reporting on progress toward Aichi Target 13 of the Strategic Plan for Biodiversity 2011–2020 and SDG Target 2.5.